Interoperator Reliability of Lung Ultrasound during the COVID-19 Pandemic - De Molo, Chiara; Consolini, Silvia; Salvatore, Veronica; Grignaschi, Alice; Lanotte, Antonella; Masi, Livia; Giostra, Fabrizio; Serra, Carla (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Aim Lung ultrasound (LUS) is a reliable, radiation-free, and bedside imaging technique used to assess several pulmonary diseases. Although COVID-19 is diagnosed with a nasopharyngeal swab, detection of pulmonary involvement is crucial for safe patient discharge. Computed tomography (CT) is currently the gold standard. To treat paucisymptomatic patients, we have implemented a “fast track” pathway in our emergency department, using LUS as a valid alternative. Minimal data is available in the literature about interobserver reliability and the level of expertise needed to perform a reliable examination. Our aim was to assess these.Materials and Methods This was a single-center prospective study. We enrolled 96 patients. 12 lung areas were explored in each patient with a semiquantitative assessment of pulmonary aeration loss in order to obtain the LUS score. Scans were performed by two different operators, an expert and a novice, who were blinded to their colleague’s results.Results 96 patients were enrolled. The intraclass correlation coefficient (ICC) showed excellent agreement between the expert and the novice operator (ICC 0.975; 0.962–0.983); demographic features (age, sex, and chronic pulmonary disease) did not influence the reproducibility of the method. The ICC was 0.973 (0.950–0.986) in males, 0.976 (0.959–0.986) in females; 0.965 (0.940–0.980) in younger patients (≤ 46 yrs), and 0.973 (0.952–0.985) in older (> 46 yrs) patients. The ICC was 0.967 (0.882–0.991) in patients with pulmonary disease and 0.975 (0.962–0.984) in the other patients. The learning curve showed an increase in interobserver agreement.Conclusion Our results confirm the feasibility and reproducibility of the method among operators with different levels of expertise, with a rapid learning curve.
Keywords: COVID-19; lung ultrasound; chest; LUS score; interoperator reliability